Meningitis caused by Candida dubliniensis in a patient with liver cirrhosis: A case report and review of the literature - Muhammad Absar; Ahmed Alduwayrij; Abdulmajeed Al-Arfaj; Zafar Shah; Fahad Nashmy; Mohamed Tahar Yacoubi (Medical Mycology Case Reports)
Candida meningitis is almost always caused by Candia albicans, but other species, such as Candida dubliniensis, can cause it on rare occasions. C. dubliniensis is increasingly linked to immunocompromised hosts but also affects immunocompetent hosts. To the best of our knowledge, we present the ninth (9th) case of C. dubliniensis meningitis, the first from Saudi Arabia. A 70-year-old woman with multiple comorbidities presented with confusion, poor oral intake, and left upper limb swelling for two weeks. C. dubliniensis was isolated and treated with liposomal amphotericin and anidulafungin. The scarcity of such infections makes the best treatment regimen undetermined. 2012 Elsevier Ltd: All rights reserved.